Reproductive Performance of Triplet-Bearing Ewes on Commercial Farms and Research Priorities Identified by Sheep Producers to Improve the Survival of Triplet-Bearing Ewes and Their Lambs - Thompson AN; Allington T; Blumer S; Cameron J; Kearney G; Kubeil L; Lockwood A; Trompf J; Winslow E; Kenyon P (MDPI (Basel, Switzerland), 2023)
Consultation with sheep producers was used to quantify the mortality of triplet-bearing ewes and their lambs, identify management practices adopted by producers to reduce these losses and prioritise future research needs to improve the survival of triplet-bearing ewes and their lambs. Surveys were completed by 64 producers across Australia who identified and separated triplet-bearing ewes from twin-bearing ewes in 2017 and/or 2018. On average, 5.9% of all ewes mated were identified as carrying triplets (6.6% of non-Merino ewes and 2.9% of Merino ewes). The average mortality of triplet-bearing ewes was 6.4%, and ewe mortality did not differ significantly between ewe breeds. The average survival of triplet-born lambs was 59%, and survival was significantly higher for lambs from non-Merino compared to Merino ewes (60.1 vs. 52.9%, p < 0.05). The key strategies adopted to reduce the mortality of triplet-bearing ewes and their lambs included management of condition score, feed-on-offer, mob size at lambing and use of shelter. There were no differences (p > 0.05) in the average mortality of triplet-bearing ewes or their lambs between producers that prioritised the adoption of certain management practices. However, significant variation existed between producers in their targets at lambing for ewe condition score (2.8 to 3.5), mob size (10 to 150 ewes) and feed-on-offer (800 to 2500 kg dry matter/ha). Overwhelmingly, the highest priorities for further research identified by producers from surveys, workshops and a webinar were ewe condition score, mob size, feed-on-offer at lambing and mineral supplementation. This study informs benchmarks for mortality of triplet-bearing ewes and their lambs under extensive grazing conditions in Australia, and the priorities for future research to reduce these losses.
Keywords: ewe mortality; lamb survival; needs analysis; producer consultation; research priorities; triplet-bearing ewes